STUDI NASKAH TERHADAP TEKS TENTANG KRITIK HADIS- HADIS IMAM MAHDI DALAM GRUP WHATSAPP KAJIAN : BELAJAR HADIS YUK - Neli Alawiah (El-Sunnah, 2022)
This study aims to examine the text on the critique of the hadiths of Imam Mahdi presented in a study in a whatsapp group: Belajar Hadis Yuk. Studying hadith is a special study of hadith whose material is delivered virtually. The research method used is qualitative research. The data search technique in this study uses observation and documentation, the purpose of observation and documentation in this study is the delivery of material whatsapp group: Belajar Hadis Yuk entitled criticism of Imam Mahdi's hadiths. The data analysis technique of this research uses a  manuscript study of the text presented in the study of hadith learning. The results of this study indicate that: Hadith study on whatsapp group Belajar Hadis Yuk talk about the Criticism of Hadiths Imam Mahdi has provided insights on group members who do not study hadith in a special institution. The study can be accessed virtually via google meet discussing the critique of the hadiths of Imam Mahdi.